Assessment Of Work-Related Stress and Anxiety Among Staff Nurses - G, Jamunarani.; R, Rajeswari.; S, Kavitha.; G, Amudha.; L, Abirami.; M, Malliga. (Journal of Neonatal Surgery, 2025)
Background: Health professionals frequently suffer from stress and anxiety owing to the characteristics and working conditions typically found in hospitals. Pressure at work can be positive leading to increased productivity. However, when this pressure becomes excessive, it has a negative impact. The individual perceives themselves as being unable to cope and not to possess the necessary skills to combat their stress and anxiety. The aim of the study was to assess the level of work-related stress and anxiety among staff nurses. Methods: The research approach selected for the study was a quantitative approach with descriptive design. Fifty staff nurses were selected through convenient sampling techniques. Demographic variables were collected by using interview questionnaires and the level of stress assessed by expanded nursing stress scale and the level of anxiety assessed by modified Hamilton anxiety rating scale. Results: Majority of work related stress was moderate 70%, and anxiety was 60%. The study reveals that there is no significant association between work related stress and anxiety among staff nurses and their selected demographic variables. Conclusion: The staff nurse had a moderate level of stress and mild level of anxiety at their workplace. Larger sample size will give a clear picture